31P magnetization transfer magnetic resonance spectroscopy: Assessing the activation induced change in cerebral ATP metabolic rates at 3 T. Issue 1 (16th March 2017) - Chen, Chen; Stephenson, Mary C.; Peters, Andrew; Morris, Peter G.; Francis, Susan T.; Gowland, Penny A.
Abstract : Purpose: In vivo 31 P magnetic resonance spectroscopy (MRS) magnetization transfer (MT) provides a direct measure of neuronal activity at the metabolic level. This work aims to use functional 31 P MRS‐MT to investigate the change in cerebral adenosine triphosphate (ATP) metabolic rates in healthy adults upon repeated visual stimuli. Methods: A magnetization saturation transfer sequence with narrowband selective saturation of γ‐ATP was developed for 31 P MT experiments at 3 T. Results: Using progressive saturation of γ‐ATP, the intrinsic T1 relaxation times of phosphocreatine (PCr) and inorganic phosphate (Pi) at 3 T were measured to be 5.1 ± 0.8 s and 3.0 ± 1.4 s, respectively. Using steady‐state saturation of γ‐ATP, a significant 24% ± 14% and 11% ± 7% increase in the forward creatine kinase (CK) pseudo‐first‐order reaction rate constant, k 1, was observed upon visual stimulation in the first and second cycles, respectively, of a paradigm consisting of 10‐minute rest followed by 10‐minute stimulation, with the measured baseline k 1 being 0.35 ± 0.04 s −1 . No significant changes in forward ATP synthase reaction rate, PCr/γ‐ATP, Pi/γ‐ATP, and nicotinamide adenine dinucleotide/γ‐ATP ratios, or intracellular pH were detected upon stimulation. Conclusion: This work demonstrates the potential of studying cerebral bioenergetics using functional 31 P MRS‐MT to determine the change in the forward CK reaction rate at 3 T. Magn Reson Med 79:22–30, 2018. © 2017 The Authors Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.